(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Giving students concise explanations is essential in the classroom to ensure they understand the material. When it comes to generalizing, students’ logical thinking is strengthened and provides guidance through inductive judgment. Regarding explanations, Leinhardt distinguished between disciplinary and instructional forms of teaching. He argues that instructional explanations aim to make concepts, procedures, events, ideas, and classes of problems clearer in order to assist students in comprehending, learning, and applying information in a flexible manner